Solvent‐Dependent Structure Formation in Drying P3HT:PCBM Films Studied by Molecular Dynamics Simulations. Issue 6 (24th October 2016) - Negi, Vikas; Lyulin, Alexey; Bobbert, Peter
Abstract : A coarse‐grained molecular dynamics based approach is used to model solvent evaporation from a supported poly(3‐hexylthiophene‐2, 5‐diyl):[6, 6]‐phenyl‐C61‐butyric acid methyl ester (P3HT:PCBM) film. Based on the different solubilities of PCBM in various solvents, P3HT‐ or PCBM‐enriched layers are found on the top surface which is in agreement with experiments. Abstract : Phase separation in the donor‐acceptor blend poly(3‐hexylthiophene‐2, 5‐diyl):[6, 6]‐phenyl‐C61‐butyric acid methyl ester (P3HT:PCBM) during evaporation of a solvent using coarse‐grained molecular dynamics simulations is studied here. To this end, an equilibrated P3HT:PCBM:solvent mixture is placed in an elongated simulation box, after which solvent molecules are removed at regular time intervals from a region above the film. Three often‐used solvents are considered: chloroform (CFM), chlorobenzene (CLB), and orthodichlorobenzene (oDCB). The coarse‐grained solvent–solvent interaction parameters are tuned to reproduce the atmospheric boiling temperatures, while the PCBM–solvent interaction parameters are tuned to reproduce the PCBM solubilities. Other parameters are taken from the literature. During evaporation, the formation of a crust that is depleted of solvent, in which aggregation of P3HT and PCBM occurs, is observed. In agreement with experiment, the top region of the dry film is rich in PCBM for the cases of CLB and oDCB, and rich in P3HT for the case of CFM, while the very top layer of the film is always rich in P3HT. This vertical separation is ascribed to a competition between the tendency of P3HT to move to the surface due to its low surface energy and the different tendencies of PCBM to be dragged along to the surface by the evaporating solvent depending on its solubility. Also in agreement with experiment, the P3HT–PCBM interface area is larger for CLB and oDCB than for CFM. For CLB and oDCB, an indication for a spinodal P3HT–PCBM decomposition starting from the top and bottom surface is found, whereas for CFM the phase separation appears to be initiated in the bulk of the film.